No one innovates more than their relationships allow: The case of small farmers - Jiménez-Carrasco, Juan Salvador; Rendón-Medel , Roberto; Díaz-José, Julio; Segura-Salazar, Citlalli Melissa (Ecosistemas y Recursos Agropecuarios, 2023)
Countering the confrontation between productive systems established by humans for food production and natural systems that support life and the climate requires the adoption of sustainable innovations, oriented towards responsible production (SDG 12) and reduction of biodiversity loss (SDG 15). This article analyzes the role of social relations in the adoption of sustainable agricultural innovations among smallholder maize farmers in the framework of a national extension process. We used paired data from 14 770 smallholders, from 2017 and 2018, in almost 50 % of Mexico's federal entities. The data were analyzed using social network indicators and a logit model. The findings show that the probability (P < 0.01) of adopting innovations from one year to the next increases if producers develop relationships with better connected actors in the network (change in radiality), expand the number of clients and have greater planted area. Producers with greater change in radiality establish patterns of adoption of sustainable innovations that allow them to maintain or improve their yields, decreasing land degradation and biodiversity loss. This implies that learning linkages are more important than other variables such as age, schooling, or farmer experience in promoting changes in innovation levels. It is advisable to reconfigure extension models to promote learning linkages and the generation of social capital.
Keywords: social network analysis; productive communication; sustainable agricultural innovations; extension services; learning linkages